Fabrication of Metallic Nano-Ring Structures by Soft Stamping with the Thermal Uplifting Method - Potejana Potejanasak; Jonglak Pahasa; Issarachai Ngamroo (My University, 2022)
In this study, the unconventional microfabrication method by the combined processes of the chemical soft stamping technique with the thermal uplifting technique to fabricate metal nanoarrays on a glass plate is proposed and their feasibility verified. The gold micro-ring arrays on a quartz glass plate are realized by utilizing a chemical template with the thermal uplifting method. Their optical properties are studied experimentally. First, a plastic mold is made of a Biaxially Oriented Polyethylene Terephthalate (BOPET) via the hot embossing method. Then, the Methanal micropatterns are transferred onto an etched surface of a substrate via a soft stamping process with a BOPET mold. The gold thin film is coated onto the methanol patterned glass plate via the Ar+ sputter coating process. Finally, the metallic micro-ring structures are aggregated on a glass plate via the thermal uplifting technique. The LSPR optical properties as the extinction spectrums of the gold micro-ring structure arrays are investigated experimentally. It is confirmed that this method was able to fabricate plasmonic micro-ring arrays with low cost and high throughput.
Keywords: Stamping; Embossing; Delamination; Nanofabrication and Lithography Techniques